Differences in Business Ethics Perception: A Developing Country Perspective - Reza, Mohammed Moin Uddin; Khatun, Asia; Rahman, Shoaib (International Journal of Business, Economics and Management, 2020)
This research paper has been developed based on study conducted on perception difference towards business ethics between final year public and private university business students of Bangladesh. A separate legal personality or ethical judgment of a business entails a business to have its own moral principles that smears to all the features of a business demeanor and is pertinent to an entire organization. Data were collected through a close-ended structured questionnaire to depict the views of business students. For analyzing collected data descriptive statistics and chi-square test is used. Result shows that public university students are more direct towards business ethics than that of private university students. Their opinion differs in the nature of business, religious view, profit-making attitude of firm, recruitment policy of a company, strictness of regulation, healthy work environment, and gender discrimination behavior of a firm. However, both the groups agreed that the overall ethical practice in business of Bangladesh is very poor and for the best compliance, some authoritarian instructions are needed.